Re-entry guidance method based on decoupling control variables and waypoint. (5th April 2019) - Li, Z.; Yang, T.; Feng, Z.
ABSTRACT: Generally, earth rotating and non-spherical perturbation of the earth in re-entry motion model are simplified using the standard trajectory guidance method. The re-entry motion is also simplified to horizontal motion and vertical motion and controlled, respectively. The simplification of re-entry motion model will lead to loss of motion accuracy and location accuracy. The direct decomposition will lead to the reduction of control accuracy because the horizontal motion and the vertical motion are coupled in re-entry. To improve the standard trajectory guidance method, the standard trajectory guidance method based on decoupling control variables and waypoint is proposed in this paper. The proposed guidance method will not simplify earth rotating and non-spherical perturbation of the earth in motion equation or decompose the re-entry motion to horizontal motion and vertical motion. Trajectory waypoint is adopted to reduce the change frequency of tracking states, because tracking states change frequently if the entire standard trajectory is tracked in real time.